Analysis of Laboratory Management Capability and Literacy Level of Science Physics Teacher - Muhammad Minan Chusni (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
The problems that arise in the school/madrasah are the weakness of the teacher's ability to prepare, manage, and carry out the physics lab. This study aims to analyze the ability of laboratory management and the level of a literacy science physics teacher. The method used in this study is literature study with the literature review of the results of research the last five years describes how the professional ability of physics teachers in managing physics laboratories and science literacy teachers in Indonesia. Based on the results of the analysis of the relevant research results that: (1) the laboratory serves to support learning by directing students to think scientific; (2) limited learning in the laboratory can lead to weak literacy of students' knowledge; (3) Implementation of physics lab activities in schools is still classified as less because of the ability of science literacy teachers in managing the laboratory has not been optimal.